More about dinosaurs - Cutts, David; Wenzel, Gregory C. (Mahwah, NJ : Troll, 1982)
Simple text and illustrations describe the environment and the characteristics of different types of dinosaurs.
School Library Journal
Booklist
2.8
K-3
Keywords: Dinosaurs; Dinosaurs